PENGARUH SAP DAN SPI TERHADAP KUALITAS LAPORAN KEUANGAN DENGAN REFOCUSINGDAN REALOKASI ANGGARAN SEBAGAI PEMODERASI - Ihyani, Layali; Handajani, Lilik; Pituringsih, Endar (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2021)
ABSTRACTThis study aims to analyze the effect of government accounting standards (SAP) and internal control systems (SPI) on the quality of regional financial reports by refocusing and reallocating budgets as moderators. The population of this research are employees in the accounting department at 43 regional apparatus organizations (OPD) of the West Lombok Regency Government. The data analysis tool uses an interaction test. The results of the study state that partially, SAP and SPI have a significant positive effect on the quality of financial reports. Then, refocusing does not strengthen the influence of SAP and SPI on the quality of financial reports. Furthermore, budget reallocation strengthens the influence of SAP on the quality of financial reports. However, budget reallocation does not strengthen the influence of SPI on the quality of financial reports. The implication of this research is that the variables in this study can be considered by the compilers of financial statements in improving the quality of the reports produced. In addition, the implications of this research can also be used as material for consideration of improving the applicable regulations related to the policy of refocusing and reallocating the budget so that needs that are considered less urgent can be refocused so that the two policies can help prepare financial statements to implement adequate SAP and SPI.Â Keywords: Government Accounting Standards, Internal Control Systems, Refocusing, Reallocating the Budget, The Quality of Financial Reports